Physical and Digital Service Quality for Sustainable Customer Satisfaction in Lapo Tuak: Evidence from South Sumatra - Clara, Catharina; Tua, Besler (Bina Nusantara University, 2025)
This study investigates the dual impact of online and offline service quality on customer satisfaction at Lapo Tuak, a traditional Batak eatery that integrates physical and digital services. Utilizing purposive sampling, data were collected from 150 respondents through structured questionnaires and analyzed using Smart PLS for structural equation modeling. The findings demonstrate that both E-Service Quality and Service Quality significantly enhance customer satisfaction, emphasizing their critical roles in fostering loyalty and repeat business. While offline interactions remain essential for building trust, the growing significance of convenient digital services, such as smooth ordering and timely delivery, cannot be overlooked. Therefore, Lapo Tuak should focus on enhancing its digital platforms while maintaining strong offline service to improve customer experiences. From a marketing perspective, promoting the ease and reliability of online delivery alongside exceptional offline service can strengthen customer loyalty and broaden the business's digital presence. This research contributes valuable insights for SMEs in the culinary sector, highlighting the importance of service quality in achieving long-term sustainability in an increasingly competitive market.